1997
DOI: 10.1017/s0033822200018890
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes of the14C Reservoir Effect in Lakes

Abstract: Conventional radiocarbon dates for sediment samples from aquatic systems and of coeval terrestrial samples deviate from each other due to the reservoir effect. The reservoir correction is usually assumed to be constant with time for a specific aquatic system. Our studies confirm that seasonal and secular changes are frequent and are governed by the limnological conditions. Lakes have two principal sources of 14C: atmospheric CO2 and the total dissolved inorganic carbon (TDIC) of the entering groundwater and ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 9 publications
7
95
1
1
Order By: Relevance
“…In addition, it is also necessary to identify whether the FRE in Lake Myvatn has remained constant through time. Geyh et al (1998) found that FREs in lakes are not necessarily constant through time and may exhibit considerable variation due to changes in physical lake parameters (i.e. surface area and water depth).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is also necessary to identify whether the FRE in Lake Myvatn has remained constant through time. Geyh et al (1998) found that FREs in lakes are not necessarily constant through time and may exhibit considerable variation due to changes in physical lake parameters (i.e. surface area and water depth).…”
Section: Discussionmentioning
confidence: 99%
“…the ratio between lake surface and lake volume (i.e. water depth), as groundwater DIC can enter the lake from the total underground surrounding the lake, while atmospheric exchange only takes place on the surface [65]. If a river, which past FRE is to be reconstructed, runs through a lake, another complicating factor is therefore added to the temporal variability of the FRE.…”
Section: Aquatic Animalsmentioning
confidence: 99%
“…A reservoir effect of 3260 years was determined based on AMS 14 C dating of modern DIC and subsequent correction for atmospheric thermonuclear bomb tests of the late 1950s-early 1960s . However, due to changes in the volume/surface ratio of the lake that took place during the deposition of the unit 1 (Hernández et al, 2008), the reservoir effect could have changed between values of 0 to 3260 years (Geyh et al, 1998). A mid point value was calculated between the two extreme reservoir ages and this value was used for constructing the age-depth model (further details in Giralt et al, 2008 and references therein).The calibration of radiocarbon dates was performed using CALIB 5.02 software and the INTCAL98 curve.…”
Section: Sedimentary Modelmentioning
confidence: 99%